Immune Profile in Patients With COVID-19: Lymphocytes Exhaustion Markers in Relationship to Clinical Outcome - Bobcakova, Anna; Petriskova, Jela; Vysehradsky, Robert; Kocan, Ivan; Kapustova, Lenka; Barnova, Martina; Diamant, Zuzana; Jesenak, Milos (Frontiers in cellular and infection microbiology, 2021)
The velocity of the COVID-19 pandemic spread and the variable severity of the disease course has forced scientists to search for potential predictors of the disease outcome. We examined various immune parameters including the markers of immune cells exhaustion and activation in 21 patients with COVID-19 disease hospitalised in our hospital during the first wave of the COVID-19 pandemic in Slovakia. The results showed significant progressive lymphopenia and depletion of lymphocyte subsets (CD3+, CD4+, CD8+ and CD19+) in correlation to the disease severity. Clinical recovery was associated with significant increase in CD3+ and CD3+CD4+ T-cells. Most of our patients had eosinopenia on admission, although no significant differences were seen among groups with different disease severity. Non-survivors, when compared to survivors, had significantly increased expression of PD-1 on CD4+ and CD8+ cells, but no significant difference in Tim-3 expression was observed, what suggests possible reversibility of immune paralysis in the most severe group of patients. During recovery, the expression of Tim-3 on both CD3+CD4+ and CD3+CD8+ cells significantly decreased. Moreover, patients with fatal outcome had significantly higher proportion of CD38+CD8+ cells and lower proportion of CD38+HLA-DR+CD8+ cells on admission. Clinical recovery was associated with significant decrease of proportion of CD38+CD8+ cells. The highest AUC values within univariate and multivariate logistic regression were achieved for expression of CD38 on CD8+ cells and expression of PD1 on CD4+ cells alone or combined, what suggests, that these parameters could be used as potential biomarkers of poor outcome. The assessment of immune markers could help in predicting outcome and disease severity in COVID-19 patients. Our observations suggest, that apart from the degree of depletion of total lymphocytes and lymphocytes subsets, increased expression of CD38 on CD3+CD8+ cells alone or combined with increased expression of PD-1 on CD3+CD4+ cells, should be regarded as a risk factor of an unfavourable outcome in COVID-19 patients. Increased expression of PD-1 in the absence of an increased expression of Tim-3 on CD3+CD4+ and CD3+CD8+ cells suggests potential reversibility of ongoing immune paralysis in patients with the most severe course of COVID-19.
Keywords: immunologic predictors; CD8-pozitivní T-lymfocyty; COVID-19; CD4-pozitivní T-lymfocyty; Pandemics; Humans; pandemie; CD8-Positive T-Lymphocytes; immune cells exhaustion; CD4-Positive T-Lymphocytes; lidé; SARS-CoV-2; clinical outcome